SISTEM INFORMASI PENJUALAN PRODUK BAJU PADA TOKO INYIAK PADANG BERBASIS WEB - Yanto, Gusrino; Anroni, Yopi Eka; Idris, Muhammad (Rang Teknik Journal, 2019)
Rapid technological developments directly or indirectly affect the trading system. At present, only by accessing the internet, we can choose the desired product, know the details of the product, and can make transactions with anyone without being limited by time and distance. The sales system at INYIAK Padang Shop is still manual, where the delivery of product information to consumers cannot be accessed directly. So a web- based sales system is needed. The method used in the development of this website is SDLC with a prototype model including needs analysis, prototype making, prototype evaluation, system coding, system testing, system evaluation and system usage. In making this system using the Sublime Text 3 text editor, XAMPP server, MySQL database and other supporting software that can facilitate the creation of this system. With the existence of this online sales information system, it can improve service systems, processing sales data and make it easier for people to get product information. The website can also create a system that is more effective and efficient in supporting the activities of this company.